Image to insight: exploring natural products through mass spectrometry imaging. Issue 7 (23rd June 2022) - Dong, Yonghui; Aharoni, Asaph
Abstract : This review provides an up-to-date summary of mass spectrometry imaging, emphasizing different applications and recent innovations in natural product research. Abstract : Covering: 2017 to 2022 Mass spectrometry imaging (MSI) has become a mature molecular imaging technique that is well-matched for natural product (NP) discovery. Here we present a brief overview of MSI, followed by a thorough discussion of different MSI applications in NP research. This review will mainly focus on the recent progress of MSI in plants and microorganisms as they are the main producers of NPs. Specifically, the opportunity and potential of combining MSI with other imaging modalities and stable isotope labeling are discussed. Throughout, we focus on both the strengths and weaknesses of MSI, with an eye on future improvements that are necessary for the progression of MSI toward routine NP studies. Finally, we discuss new areas of research, future perspectives, and the overall direction that the field may take in the years to come.